2010
DOI: 10.1111/j.1526-4637.2010.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Pharmacokinetics of Fentanyl Buccal Soluble Film

Abstract: ObjectiveThe objectives of the study were to determine the absolute bioavailability of fentanyl from fentanyl buccal soluble film, estimate the percentage of a fentanyl dose absorbed through the buccal mucosa, and compare the bioavailability of equivalent doses administered either as single or multiple dose units.DesignOpen-label, randomized, four-period, Latin-square crossover pharmacokinetic study.SettingInpatient phase 1 unit.PatientsTwelve healthy volunteers.InterventionsInjectable fentanyl citrate (200 µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 11 publications
0
35
0
1
Order By: Relevance
“…administration is few. An IV administration of 200 μg FEN was conducted on humans, this study reported the pharmacokinetic parameters as follows; (C max ) of 1.46 ± 0.66 ng/mL, median (T max ) of 0.17 hours and (T 1/2 ) of 18.03 ± 10.08 hours [14]. This data shows a widely different change compared to rat, which can be ascribed to many factors; first: the different rout of administration and small blood volume of rat compared to human, second: amount of fatty tissue that enhance the distribution of FEN as it is considered to be highly lipophilic drug.…”
Section: Pharmacokinetics Of Fen In Ratsmentioning
confidence: 99%
“…administration is few. An IV administration of 200 μg FEN was conducted on humans, this study reported the pharmacokinetic parameters as follows; (C max ) of 1.46 ± 0.66 ng/mL, median (T max ) of 0.17 hours and (T 1/2 ) of 18.03 ± 10.08 hours [14]. This data shows a widely different change compared to rat, which can be ascribed to many factors; first: the different rout of administration and small blood volume of rat compared to human, second: amount of fatty tissue that enhance the distribution of FEN as it is considered to be highly lipophilic drug.…”
Section: Pharmacokinetics Of Fen In Ratsmentioning
confidence: 99%
“…The inactive layer isolates the bioadhesive layer from the buccal cavity, minimizing the amount of fentanyl that is swallowed and facilitating delivery directly to the buccal mucosa. [27][28][29] Once applied FBSF starts to dissolve in minutes and is completely dissolved within 15 to 30 minutes without patient effort. It requires a minimal quantity of saliva.…”
Section: Fentanyl Buccal Soluble Filmmentioning
confidence: 99%
“…It has a BioErodible MucoAdhesive (BEMA ® ; BioDelivery Sciences, Inc., Raleigh, NC) delivery technology. 14,[27][28][29] This technology consists of two different layers made of water-soluble polymeric films, one bioadhesive layer and one inactive layer. The bioadhesive layer contains fentanyl citrate that adheres within seconds of making contact with the moist buccal mucosa.…”
Section: Fentanyl Buccal Soluble Filmmentioning
confidence: 99%
See 2 more Smart Citations